PARTIAL DIFFERENTIAL EQUATIONS an introduction. - Shah, Nita H.; Jani, Mrudul Y. ([S.l.] : CRC PRESS, 2020)
Differential equations play a noticeable role in engineering, physics, economics, and other disciplines. They permit us to model changing forms in both mathematical and physical problems. These equations are precisely used when a deterministic relation containing some continuously varying quantities and their rates of change in space and/or time is recognized or postulated. This book is intended to provide a straightforward introduction to the concept of partial differential equations. It provides a diversity of numerical examples framed to nurture the intellectual level of scholars. It includes enough examples to provide students with a clear concept and also offers short questions for comprehension. Construction of real-life problems is considered in the last chapter along with applications. Research scholars and students working in the fields of engineering, physics, and different branches of mathematics need to learn the concepts of partial differential equations to solve their problems. This book will serve their needs instead of having to use more complex books that contain more concepts than needed.
OCLC-licensed vendor bibliographic record.
Keywords: Differential equations, Partial; MATHEMATICS / Applied; BUSINESS & ECONOMICS / Operations Research; TECHNOLOGY / Operations Research